Assessing Dermatological Health Needs in Rural Communities - Katheryn Bell; Victoria Snook; Braden Baker; Andrea Wright; Jay Wolverton (Journal of Student-Run Clinics, 2025)
Background: Rural communities face significant barriers to dermatologic care, including geographic isolation and financial constraints. These challenges contribute to delayed diagnoses, suboptimal management, and exacerbated health disparities. Rural student-run free clinics (SRFCs) provide essential services, but limited data exist on the specific dermatologic needs and barriers of these communities. This study aims to assess the dermatologic health needs, care barriers, and healthcare-seeking behaviors of rural patients attending an SRFC.Methods: An anonymous 19-question survey was distributed via an electronic survey and data analysis software named Research Electronic Data Capture to individuals aged 18+ attending a rural SRFC. The survey collected data on demographics, dermatologic conditions, access to care, treatment and prevention strategies, and sources of dermatologic health education. Descriptive statistics were used to analyze trends in dermatologic care access, financial barriers, and information-seeking behaviors. Spearman rank correlation assessed income–dermatology access associations (α=0.05).Results: Among 42 participants, 26.0% were aged 26-35, and 69.0% were female. Acne (38.5%) and eczema (23.1%) were the most reported conditions. Only 60.0% of those with a diagnosed condition had confirmed access to dermatologic care. Income did not correlate with care access (Spearman r = 0.27, p = 0.189). Geographic barriers persisted, as 50.0% of respondents were uncertain whether dermatology services were available locally. Younger participants (18-35) primarily relied on internet searches and social media for dermatologic information, while older participants (56+) consulted healthcare providers. Among participants earning $60,000-$90,000, 100% had access to dermatologic care, but 75% had never sought care regularly. Uncertainty about access was highest among lower-income groups.Conclusions: Rural populations experience significant uncertainty about dermatologic care availability, contributing to delayed treatment. Financial barriers and reliance on non-medical information sources hinder effective care utilization. Targeted educational initiatives and improved access strategies, such as SRFCs, can reduce care disparities.